2010
DOI: 10.1111/j.1750-3841.2009.01487.x
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Water/Oil/Water Emulsions Stabilized by Polyglycerol Polyricinoleate and Whey Protein Isolate

Abstract: In this study we tried to prepare stable water-in-oil-in-water (W/O/W) emulsions using polyglycerol polyricinoleate (PGPR) as a hydrophobic emulsifier and whey protein isolate (WPI) as a hydrophilic emulsifier. At first, water-in-oil (W/O) emulsions was prepared, and then 40 wt% of this W/O emulsion was homogenized with 60 wt% aqueous solution of different WPI contents (2, 4, and 6 wt% WPI) using a high-pressure homogenizer (14 and 22 MPa) to produce W/O/W emulsions. The mean size of final W/O/W droplets range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 26 publications
2
28
0
1
Order By: Relevance
“…2) and a smaller (P < 0.05) mean droplet size (Table 3) than the emulsion formulated with WP. Mun et al (2010) reported that the mean size of W 1 /O/W 2 emulsions prepared with different concentrations of PGPR and whey protein isolate ranged from 3.3 to 9.9 lm, similar to this experiment.…”
Section: Microscopysupporting
confidence: 83%
See 2 more Smart Citations
“…2) and a smaller (P < 0.05) mean droplet size (Table 3) than the emulsion formulated with WP. Mun et al (2010) reported that the mean size of W 1 /O/W 2 emulsions prepared with different concentrations of PGPR and whey protein isolate ranged from 3.3 to 9.9 lm, similar to this experiment.…”
Section: Microscopysupporting
confidence: 83%
“…Monomodal (Choi et al, 2009;Mun et al, 2010), bimodal (Hemar et al, 2010;O'Reagan and Mulvihill, 2009;Su et al, 2006) or even trimodal (Surh et al, 2007) particle size distributions have been reported in double emulsions. However, bimodal distribution occurs most characteristically when caseinate is used as a hydrophilic emulsifier (Hemar et al, 2010;O'Reagan and Mulvihill, 2009;Su et al, 2006).…”
Section: Particle Size Distributionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, microspheres prepared using the W/O/W method (Gallarate et al, 2009;Liu et al, 2006;Mun et al, 2010;Yin et al, 2006) have two major problems: a low drug loading efficiency and burst release behavior (Freiberg et al, 2004;Huang and Brazel, 2001;Park et al, 1992a, b;Wang et al, 1991).…”
Section: Resultsmentioning
confidence: 99%
“…34,[84][85][86] The use of a 'bioemulsifier' to prepare W/O/W emulsions by the two-step procedure was reported more than 30 years ago. 87 In the intervening period, various different types of food protein emulsifiers have been employed in the stabilization of double emulsions, including sodium caseinate, 53,64,68,69,72,73,[88][89][90] gelatin, 66,91 BSA 63 and whey protein isolate 92 and also some hydrocolloid emulsifiers such as gum arabic 71,93 and hydrophobically modified starch. 30 Attempts have also been made to stabilize the outer droplets of double emulsions with various soluble polysaccharides 84,85,94,95 acting as thickening/gelling agentsProtein concentration (wt%) Yield (%) pectin, carrageenan, alginate, xanthan, gellan, locust bean gum and carboxymethylcellulose-and also using colloidal particles of microcrystalline cellulose.…”
Section: Stabilization Of Outer Droplets Of W/o/w Emulsions By Biopolmentioning
confidence: 99%